Moving Up the Sanitation Ladder: A Study of the Coverage and Utilization of Improved Sanitation Facilities and Associated Factors Among Households in Southern Ethiopia - Abel Afework; Hunachew Beyene; Adane Ermias; Aiggan Tamene (SAGE Publishing, 2022)
Background: Improved sanitation facilities offer numerous advantages, ranging from the reduction of diarrheal illnesses and helminth infections to the improvement of psychosocial well-being. At the household level, attaining universal access to improved sanitation facilities demands a thorough understanding of the factors that influence their adoption and use. As a result, the purpose of this study was to assess the availability and utilization of improved sanitation facilities, as well as the factors that influence the adoption and proper use of such a facility among households in the Gedeb district of Southern Ethiopia. Methods: A community-based cross-sectional household survey was conducted from March to April 2019. A systematic random sampling technique was used to select 630 households at random. A pre-tested questionnaire was used to collect the respondents' self-reported data, which comprised socio-demographic, home characteristics, behavioral, and environmental elements. The factors related to the availability and utilization of improved sanitation facilities were identified using multivariable logistic regression. Result: Improved sanitation facilities were present in 172 (27.3%) of the 630 households surveyed, with 111 (64.5%) of them being used properly. The availability of improved sanitation was associated with educational status [AOR = 2.73, 95% CI (1.59, 4.67)], upper wealth quintile [AOR = 2.18, 95% CI (1.21, 3.93)], ever hearing educational messages about latrines [AOR = 3.9, 95% CI (1.86, 8.18)], favorable attitude toward latrine construction [AOR = 2.81, 95% CI (1.67, 4.74)], and receiving support during construction [AOR = 3.78, 95% CI (2.15, 6.65)]. Furthermore, utilization was associated with the absence of children under the age of 5, knowledge of sanitation-related diseases, and a positive attitude toward latrine use. Conclusion: Both the availability of improved sanitation facilities and the rate at which they were used properly fell far short of the National Hygiene and Environmental Health Strategy's goals. This study contributes to the body of knowledge on how to improve the availability of improved sanitation in Ethiopia.